2006
DOI: 10.1002/pon.1028
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and sociodemographic correlates of benefit-finding in men treated for localized prostate cancer

Abstract: Active coping strategies and greater perceived social support are important correlates of greater BF following localized PCa treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 37 publications
8
50
2
1
Order By: Relevance
“…The sample were all white, married or in relationships, not economically disadvantaged and of a younger age range than is typically representative of prostate cancer, as most cases are diagnosed in men aged over 65 (Cancer Research UK, 2013). This is relevant in that differences have been found in coping styles between older and younger men with prostate cancer (Roesch et al, 2005), based on income, education levels and ethnicity (Kinsinger et al, 2006) and quality of life may be influenced by relationships status (Gore et al, 2005). There is a sampling bias inherent in the fact that participants were self-selected as using coping strategies to maintain their emotional wellbeing and were also recruited from a pool of charity volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The sample were all white, married or in relationships, not economically disadvantaged and of a younger age range than is typically representative of prostate cancer, as most cases are diagnosed in men aged over 65 (Cancer Research UK, 2013). This is relevant in that differences have been found in coping styles between older and younger men with prostate cancer (Roesch et al, 2005), based on income, education levels and ethnicity (Kinsinger et al, 2006) and quality of life may be influenced by relationships status (Gore et al, 2005). There is a sampling bias inherent in the fact that participants were self-selected as using coping strategies to maintain their emotional wellbeing and were also recruited from a pool of charity volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Carver and Antoni (2004) reported in a longitudinal study that initial PTG predicted a higher quality of life five to eight years after diagnosis in breast cancer patients. In spite of these results, most studies have not revealed any significant associations between HRQoL and PTG (Dunn et al 2011;Kinsinger et al 2006;Park et al 2010). …”
mentioning
confidence: 82%
“…Although the difference between one concept and the other is still a matter of debate (Kinsinger et al, 2006;Park & Hegelson, 2006), certain authors tend to assume that PTG is a type of perceived benefit (BF); (Kinsinger et al, 2006;Siegel, Schrimshaw & Pretter, 2005). Thus, in these studies BF is defined as: the fact to find benefits (or positive consequences) in personal, social, psychological and/or spiritual domains, after having suffered a trauma or having experienced a highly adverse situation (Kinsinger, et al, 2006).…”
Section: Benefit Findingmentioning
confidence: 99%
“…Thus, in these studies BF is defined as: the fact to find benefits (or positive consequences) in personal, social, psychological and/or spiritual domains, after having suffered a trauma or having experienced a highly adverse situation (Kinsinger, et al, 2006).…”
Section: Benefit Findingmentioning
confidence: 99%